What matters most to older adults in treatment decision making: A discrete choice experiment - Vera C. Hanewinkel; Hanneke van der Wal-Huisman; Suzanne Festen; Richte CL Schuurmann; Goudje L. van Leeuwen; Maria-Annette Kooijman; Marijke J. Nogarede; Barbara L. van Leeuwen; Daan Brandenbarg (PLoS ONE, 2025)
Introduction Medical decision making is often guided bydisease-specific outcomes such as life extension or survival. Especially for older adults other outcomes like maintaining independence can be equally vital or more important. Enhanced insight into the priorities of community dwelling older adults can optimize treatment decision making and refine healthcare policy. The aim of this study was is to identify which outcomes are prioritized by adults of 50 years and older when choosing between treatment options with various outcomes in a hypothetical case of a life-threatening disease. Methods We conducted a Discrete Choice Experiment (DCE) with individuals aged ≥50, comparing six pairs of hypothetical treatmentoptions with five attributes: life expectancy, independence, pain, memory complaints and societal costs. Attribute utility was analyzed using a conditional logit model, and latent class analyses were employed to explore preferences in groups. Data collection took place at a four-day national fair for people aged 50 or older in Utrecht, Netherlands. Results In total 333 volunteers (233 female, mean 70 yr, SD 7.7) completed the DCE. Most participants prioritized maintaining independence, followed by life expectancy and the avoidance of severe physical or cognitive impairments (p < .05). Life expectancy only had a positive impact when it was extended by two years. Avoiding high societal costs also influenced preferences. Latent class analysis identified two subgroups: one (approximately 25% of participants) prioritized life expectancy, willing to compromise on other factors, while the other emphasized independence and minimizing societal costs. Interaction tests between respondents’ characteristics and preferences showed no significant differences. Conclusions When confronted with a (possible) life threatening disease, most people aged ≥ 50 yr prioritize remaining independence and the absence of severe pain and severe memory complaints above life expectancy. A smaller subgroup prioritized life expectancy above other attributes. These attributes – including societal costs – should be taken in to account in individual treatment decision making, in clinical guidelines and national healthcare policy.